(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Increasing the efficacy of teachers is the most effective approach for boosting student performance. The process of becoming a good teacher begins with adequate preparation and continues during the first several years in the classroom. We need to encourage the appropriate individuals to become teachers, provide them with the very best training that is available, and provide support for them as they transition into the classroom. Perception that the training programme will assist them in becoming more competitive in higher education. It has been discovered that the majority of participants joined the training programme in order to become research and technically sound with improved interpersonal and technical skills, and it has also been discovered that training and development programmes are effective in meeting the needs of participants. Different variables that were used in the questionnaires were separated into four categories with the approval of renowned academicians and researchers in order to facilitate the researcher’s goal of determining the impact that SCERT has had on the teaching and research conducted within higher education. After the assessment of the effectiveness of training was completed, it was determined that the programmes that are coordinated by DIET’s are beneficial and successful in developing the research and teaching skills of higher education instructors.